Changes in workload of Chinese university undergraduate teaching from the perspective of education quality management: A case study of a teaching-research university - Sun Lizhi; Chen Danhui; Xu Jingjing (International Journal of Metrology and Quality Engineering, 2023)
The teaching workload of university teachers is an objective reflection of their instructional input and directly affects the quality of education and teaching. The ultimate goal of studying university teachers' workload is to enhance the quality of higher education. Based on the analysis of data from twelve years' teaching workload of a teaching-research university in China, the results show that the changes of overall teaching workload are in stages. Classroom teaching workload is the majority of the whole teaching workload. The teaching workload is mainly undertaken by university teachers with intermediate and deputy senior professional titles, and changes in teaching workload undertaken by university teachers with junior professional title and intermediate professional title is greater than those with vice senior professional title and senior professional title. Male teachers' workload is slightly more than female teachers, but gender differences have been shrinking over the years. The proportion of classroom teaching workload in teaching-oriented colleges is high, which is about 7:3 and has decreased in the past twelve years. Developing logic, administrative logic and difference logic are generative logic of changes in undergraduate teaching workload. Due to the relevance of the ISO 9000 family of standards in the management of higher education teaching, it is recommended to follow its seven quality management principles and adopt a teaching quality management approach based on the PDCA cycle in a broader context of quality management. This approach aims to manage higher education systematically, establish an organizational environment, and promote teachers' active engagement in teaching, including teaching workload. It also facilitates to improve teacher classification management and evaluation mechanisms.